Comparison of effects of volume-controlled equal inspiratory-to-expiratory ratio (1:1) ventilation with conventional ratio (1:2) ventilation on respiratory mechanics and hemodynamics in patients undergoing upper abdominal laparoscopic surgeries: A randomized clinical trial - Prathap Gunasekaran; Ramyavel Thangavelu; Sivakumar Segaran (Journal of Current Research in Scientific Medicine)
Background: Patients undergoing laparoscopic surgeries are often at risk of developing hypoxemia, increased airway pressure, and barotrauma due to pneumoperitoneum. Prolongation of inspiratory time in a respiratory cycle has been found to improve oxygenation without any increase in peak airway pressure. Hence, we studied the effect of equal ratio volume-controlled ventilation on the mechanics of respiration and hemodynamics in comparison with conventional ratio volume-controlled ventilation. Materials and Methods: Seventy-six general surgical patients aged 18–70 years of age belonging to the American Society of Anaesthesiologists (ASA) I and II posted for upper abdominal laparoscopic surgeries were randomly allocated to two groups. Group A patients were ventilated with volume-controlled 1:1 ventilation whereas Group B patients were ventilated with 1:2 ratio ventilation. Intraoperatively, parameters of respiratory mechanics that included peak airway pressure, mean airway pressure, end-tidal carbon dioxide, and hemodynamics (MAP and heart rate) were recorded. The parameters measured were compared between the two groups using repeated measures ANOVA. Results: There were no significant differences in peak airway and MAPs recorded between the two groups (P = 0.82 and P = 0.51, respectively). The hemodynamic parameters, saturation, and end-tidal carbon dioxide measurements also remained similar between the two groups. Conclusion: Volume-controlled equal ratio ventilation was found to be similar to conventional ratio ventilation in terms of parameters of respiratory mechanics and hemodynamics in patients undergoing upper abdominal laparoscopic surgeries.